The impact of mind–body exercise on the quality of life in older adults: the chain mediation effect of perceived social support and psychological resilience - Yang, Qingqing; Zhang, Yinkai; Li, Shiying (Frontiers in Public Health, 2024)
Background With the intensification of the global aging trend, there is a contradiction between the extended lifespan and the decline of physiological functions among the older adult. It has become a global consensus to focus on and improve the quality of life for the older adult. Mind–body exercises (Tai Chi, Ba Duan Jin, Yi Jin Jing) play a crucial role in promoting the quality of life for older adults, but the mechanisms and mediating effects are not yet clear. Objective This study examines the impact of mind–body exercises (Tai Chi, Ba Duan Jin, Yi Jin Jing) on the quality of life in older adults, with a particular focus on exploring the chain mediating effects of perceived social support and psychological resilience. Methods This study is a cross-sectional study that surveyed 1,087 older adults participating in mind–body exercises (Tai Chi, Ba Duan Jin, Yi Jin Jing) in 13 districts of Beijing, China, from March 25 to May 3, 2024. The Physical Activity Rating Scale (PARS-3), the World Health Organization Quality of Life Scale (WHOQOL-BREF), the Perceived Social Support Scale (PSSS), and the Connor-Davidson Resilience Scale (CD-RISC) were used to measure mind–body exercise, perceived social support, psychological resilience, and quality of life, respectively. Data were statistically analyzed using SPSS 26.0, and mediation effects were tested and effect analysis was conducted through structural equation modeling (AMOS) and the Bootstrap method. Results The study results show that mind–body exercises (Tai Chi, Ba Duan Jin, Yi Jin Jing) are significantly and positively correlated with the quality of life in older adults (r = 0.549, p < 0.01). The path coefficients for the relationships mind–body exercise → perceived social support (β = 0.46, p < 0.001) → psychological resilience (β = 0.20, p < 0.001) → quality of life in older adults (β = 0.39, p < 0.001) are significant, indicating that perceived social support and psychological resilience have a chain mediating effect between mind–body exercise and the quality of life in older adults. Conclusion Mind–body exercises not only improve the quality of life for older adults but also indirectly enhance it by strengthening perceived social support and psychological resilience. This study provides significant reference for developing health intervention strategies targeted at older adults, suggesting that promoting mind–body exercises can improve their sense of perceived social support and psychological resilience, thereby increasing their quality of life.